Penerapan Early Warning Score (EWS) dalam Mendeteksi Dini Perburukan Kondisi Pasien Covid-19 - Dally Rahman; Emil Huriani; Elvi Oktarina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The high mortality rate of Covid-19 is a problem for the government and health services that were influenced by treatment strategy at the hospital. Covid-19 patients can experience a sudden severe condition without apparent symptoms known as